A Study on the Effectiveness of Online Middle School English Teaching in Post-Epidemic Context: An Example from Anyi Second Middle School - Dr. Jie John Seaver Zhou (Global Journal of Human-Social Science, 2023)
Under the influence of the epidemic Classroom in the Air has been launched in primary and middle schools and kindergartens across the country since February 10 2020 The popularity of online teaching model undoubtedly brings a new opportunity for teaching under the new coronavirus epidemic making online teaching rapidly promoted and popularized in a short time At present with the advent of the post-epidemic era profound changes have taken place in education and teaching Online teaching has become a trend and English as an important subject should keep pace with The Times This paper studies the effects of online English teaching in the context of the epidemic aiming to analyze the problems existing in the process of online teaching and the solutions Taking the Grade 8 students of Anyi Second Middle School as Survey objects the author analyzed the characteristics of online teaching and studied the teaching effect of English subject in the background of the epidemic Firstly we consulted relevant literature to understand the research status of junior high school English under the background of the epidemic